PENGEMBANGAN MODUL BERBASIS GAMBAR KEJADIAN RIIL UNTUK PEMBELAJARAN FISIKA SMA - Nuri Tika Sari; Sutarto Sutarto; Subiki Subiki (FKIP Universitas Jember, 2017)
Development of real events image-based module is a develop of material on physics learning that presents real events images or physics phenomenon that are used to clear up a physics concepts to make it easier to be learnt by students independently.The purposes of this research are to describe the validity of real events image-based module, students’ learning achievement, and students’ learning activities. This type of research is the development, use research design Borg and Gall. Data collection techniques used are sheets of validation, observation, interview and test. Real events image-based module is said good and decent to be used for teaching physics in senior high school if the product’s validity has been tested through logic validity and user validity. Real events image-based module is valid if the logic validity and user validity are > 60,00%. Conclution of this research are : (1) logic validity and user validity real events image-based module are 85,15% and 90,23% with a very valid category. (2) Student’ learning achievement after using real events image-based module is 84,8 with a very good, and (3) students’ learning activities using real events image-based module is 88,5% with a very active. Keyword : Real events image-based module, learning achievement, learning activities, validity